文字层面的词汇扩散现象 = A study of Lexical Diffusion in Chinese characters - 赖佳瑜 Lai, Chia Yee (2010)
In general, the majority of academic scholars tend to put their efforts in researching the stages before and after the change in the study of the evolution of Chinese characters, while often overlooking the intermediate process of change in between the two stages. As a result, the change that they observed was one which seemed to happen overnight. In these recent years, Huang Wen Jie (2008), through his observation of the process of change of the character shuǐ 水 in composite characters from Qin to Pre-Han period, pointed out that the process of change did not affect the whole set of relevant characters in one go. However, his objective was to prove that Chinese characters in this period were undergoing the transition from ancient characters to modern characters. Hence, he has never brought forth the idea that the speed of change of different characters in between the pre-change and post-change stages might be different. This thesis mainly focuses from the evolutionary perspective, the research of a few selected characters from oracle bone inscriptions to clerical scripts as case studies. These characters are fù 阜, shuǐ 水, yuè 月 and ròu 肉. In the study, we will observe the changing behaviors of the characters in question when they appear in different composite characters, emphasizing the speed of change of these composite characters in between the pre-change and post-change stage. This thesis shall apply the theory of Lexical Diffusion (LD)—a theory which has successfully explained sound change—to the evolution of Chinese characters, providing a fresh research perspective to our research topic. According to our data, most of the changes occurred in the Qin and Han clerical scripts. However, we notice that the changes do not affect all the characters at once. Under the same conditions, some words have changed, some are still in the process of changing, while others remain unchanged. This phenomenon is in line with the hypothesis made by the theory of Lexical Diffusion.